(untitled) (Research, Society and Development, 2023)
The article aims to analyze the digital minting process of a cryptocurrency derived from Ethereum, this work aims to demonstrate the reduction of energy consumption in the creation of this cryptocurrency. This article also contributes to the growth of work that will be carried out in the future in the crypto asset segment. That said, this study addresses all the steps related to creation, which had the following phases from opening a digital wallet for storage, to minting, defining the amount and network as the basis for the constitution of a cryptocurrency. The methodology used was the qualitative method, this method describes the empirical knowledge that involves the concept and definitions of new crypto asset technologies. It was possible to conclude that, from the networks analyzed in the process of minting and energy consumption, Ethereum contributes in a more beneficial way to its users and the environment. To complete these benefits, Ethereum will support 100,000 transactions per second in version 2.0, in addition, it will need less computational power for validation, it also aims at efficiency in the energy needed to validate operations, which causes less electrical energy spent, therefore, there is much less energy consumption, moreover in a more concrete way, decentralization and price appreciation.